Digital imaging and qPCR analysis and comparison of short-term plaque removal effects of toothbrushing - Luo, Yuanyuan; Wang, Danni; Li, Yuxiao; Geng, Dezhi; Yu, Bei; Zhao, Yueping; Xiang, Qi (Frontiers in Dental Medicine, 2023)
Purpose Digital imaging technology and a real-time fluorescent quantitative polymerase chain reaction (RQ-PCR) were used to determine the changes in dental plaque caused by different toothbrushing tools. Methods A total of 120 subjects were selected and divided into four groups: a manual toothbrush group, a manual toothbrush combined with an oral irrigator group, an electric toothbrush combined with an oral irrigator group, and an electric toothbrush group. We compared the changes in plaque count, plaque area, and colony colonization of the four groups after different cleaning tools had been used for a period of time. Results Dental plaque count and plaque area decreased in all four groups. The decreases in plaque count and Streptococcus mutans in the electric toothbrush combined with an oral irrigator group were significantly higher than those in other groups. Conclusion Electric toothbrush combined with an oral irrigator shows a good result for plaque removal effect. Digital image analysis combined with biological methods can be used to evaluate dental plaque.